2015
DOI: 10.1007/s12630-015-0368-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dexmedetomidine on postoperative shivering: a meta-analysis of clinical trials

Abstract: Purpose Shivering is a frequent complication in the postoperative period. The aim of the current meta-analysis was to assess the efficacy of dexmedetomidine on postoperative shivering. with a minimum effective dose of 0.5 lgÁkg -1 (RR = 0.36; 95% CI: 0.21 to 0.60). The anti-shivering effect can be achieved both intravenously and epidurally when administered within two hours prior to the end of surgery. The efficacy of dexmedetomidine was similar to widely used anti-shivering agents, such as fentanyl, meperidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 42 publications
5
34
0
Order By: Relevance
“…24) Prevention of shivering by administration of intravenous dexmedetomidine in a parturient may be limited by its principal side-effects, i.e., hypotension and bradycardia. 9) Several studies have shown that use of intrathecal dexmedetomidine as an adjuvant to hyperbaric bupivacaine is associated with prolonged motor and sensory block, while maintaining the hemodynamic stability. [25][26][27] Recent studies have shown that dexmedetomidine may be safely used as an intrathecal supplement in Cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24) Prevention of shivering by administration of intravenous dexmedetomidine in a parturient may be limited by its principal side-effects, i.e., hypotension and bradycardia. 9) Several studies have shown that use of intrathecal dexmedetomidine as an adjuvant to hyperbaric bupivacaine is associated with prolonged motor and sensory block, while maintaining the hemodynamic stability. [25][26][27] Recent studies have shown that dexmedetomidine may be safely used as an intrathecal supplement in Cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
“…7,8) However, a recent meta-analysis of clinical trials demonstrated that intravenous dexmedetomidine was not optimal for prevention of shivering due to its potential side effects. 9) More importantly, the use of i.v. dexmedetomidine to facilitate Cesarean delivery in the parturient population has been reported in several case reports, including in a woman with primary pulmonary hypertension, 10) and in another with spinal muscular atrophy.…”
mentioning
confidence: 99%
“…This result is similar with some previous studies. 6,10 Bakri et al 32 indicated that DEX could reduce the incidence and severity of postoperative nausea. However, TSA in this article showed that firm conclusion can be drawn because Z curve crossed both the conventional boundary and the TSA boundary.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients undergoing various surgeries were included, and only a few studies provided nausea, vomiting, and shivering information. In 2014, a meta-analysis made by Liu et al 10 indicated that DEX may not be appropriate solely for the purpose of the prevention of postoperative shivering due to the high price and potential adverse events, but they also included patients undergoing various surgeries and did not make a subgroup analysis on different surgeries. It was reported that laparoscopy was one of the main factors associated with an increased risk of postoperative PONV.…”
Section: Introductionmentioning
confidence: 99%
“…But compared to clonidine, dexmedetomidine is costlier and has got side effects like bradycardia, dry mouth and sedation. 6 Clonidine has been tried in oral as well as intravenous route for premedication in hypotensive anaesthesia.…”
Section: Discussionmentioning
confidence: 99%